ภาษา การสื่อสาร และพุทธจริยธรรม: มิติใหม่ของพระสงฆ์ในพื้นที่สื่ออนไลน์ - กาญจนกิจจา, ปกาน; (บุญศรี), พระภัทรพล จตฺตมโล; โทอื้น, วรเชษฐ์ (วารสาร มมร ยศสุนทรปริทรรศน์; Vol 2 No 3 (2025): วารสาร มมร ยศสุนทรปริทรรศน์ ปีที่ 2 ฉบับที่ 3 : กันยายน - ธันวาคม 2568, 2025)
In the context of contemporary digital society, the transformation of information technology has compelled Thai Buddhist monks to adapt to new modes of communication particularly through online platforms that have become vital channels for disseminating the Dhamma, delivering sermons, and engaging with younger Buddhist audiences. This article explores the interrelationship among language, communication, and Buddhist ethics as new dimensions of the monastic role in online media spaces. It adopts both linguistic and ethical perspectives through case analyses of monks who employ social media platforms such as Facebook, YouTube, and TikTok to communicate Buddhist teachings in ways relevant to modern society. The findings reveal that monastic language in online communication demonstrates a deliberate synthesis of “Dhamma language” and “contemporary common language,” enhancing accessibility across diverse age groups and cultural backgrounds. Dhamma communication, therefore, extends beyond traditional preaching to encompass digital media formats such as short video clips, dialogues, and inspirational content. Nevertheless, ethical challenges persist—such as maintaining verbal restraint, preventing distortion of Dhamma principles, and safeguarding the sanctity of the monastic institution in fast-evolving digital contexts. This study proposes the conceptual framework of Buddhist Communication Ethics as a core paradigm for enhancing monks’ communicative competence in the digital age. Through mindful, wise, and compassionate language use, monastics can foster mutual understanding, social harmony, and moral cultivation, thereby contributing to the creation of digital spaces conducive to learning, ethical reflection, and sustainable spiritual development in the 21 st century.